2008
DOI: 10.1088/0957-4484/19/29/295103
|View full text |Cite
|
Sign up to set email alerts
|

Preferential killing of cancer cells and activated human T cells using ZnO nanoparticles

Abstract: Nanoparticles are increasingly being recognized for their potential utility in biological applications including nanomedicine. Here we examine the response of normal human cells to ZnO nanoparticles under different signaling environments and compare it to the response of cancerous cells. ZnO nanoparticles exhibit a strong preferential ability to kill cancerous T cells (∼28-35×) compared to normal cells. Interestingly, the activation state of the cell contributes toward nanoparticle toxicity, as resting T cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
382
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 580 publications
(409 citation statements)
references
References 31 publications
(54 reference statements)
12
382
0
2
Order By: Relevance
“…All three epithelial cancer cell lines were less prone to silica NP induced injury, which may be due to the higher rate of cell division and the associated dilution of cellular NP levels 163 . Another study by Hanley et al however showed a higher susceptibility to ZnONP injury for activated primary human T lymphocytes in comparison to resting human T lymphocytes, as can be seen in Figure 4b 161 . This preferential targeting of rapidly dividing cells can in turn be coupled to a higher uptake of the NPs in actively proliferating cells 164 .…”
Section: Cell Lines Primary or Stem Cellsmentioning
confidence: 79%
See 1 more Smart Citation
“…All three epithelial cancer cell lines were less prone to silica NP induced injury, which may be due to the higher rate of cell division and the associated dilution of cellular NP levels 163 . Another study by Hanley et al however showed a higher susceptibility to ZnONP injury for activated primary human T lymphocytes in comparison to resting human T lymphocytes, as can be seen in Figure 4b 161 . This preferential targeting of rapidly dividing cells can in turn be coupled to a higher uptake of the NPs in actively proliferating cells 164 .…”
Section: Cell Lines Primary or Stem Cellsmentioning
confidence: 79%
“…First, the degree of association between the NP and the cell membrane is known to be crucial as it influences NP uptake levels 161 . The physiological function of the cell also appears to be important with regard to NP uptake, as for example macrophages and monocytes mostly show higher uptake and are therefore more susceptible to nanotoxicity, which can be linked to the phagocytotic uptake mechanism and the capacity to clear xenobiotics from the body 154,155,162 .…”
Section: Cell Lines Primary or Stem Cellsmentioning
confidence: 99%
“…We validated the sensitivity of the assay through testing the selective phosphatidylinositide 3-kinase (PI 3-kinase) inhibitor LY294002, known to inhibit glioblastoma proliferation, migration, and invasion in both cell culture and rodent xenograft models. [20][21][22] We also assessed novel zinc oxide nanoparticles (ZnO NPs), which demonstrate selective toxicity toward cancer cells in vitro, 23 for conserved preferential anticancer efficacy in vivo in this refined zebrafish xenograft assay.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has come to light that these can be engineered and exploited for various applications in biomedical field, diagnostics, therapeutics, drug delivery imaging and bio-signalling (Ghosh et al, 2008;Sperling et al, 2008;Hanley et al, 2008;Seo et al, 2006;Visaria et al, 2006). 'Nanoparticles' (NPs) are the particles which range in nanosize usually from 1 -100 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers are focussing on therapeutical use of NPs to reduce treatment duration, flexibility in choosing administration route and for enhancing the activity of drugs, so that the drugs can be used even in case of deadly diseases like Tuberculosis (TB) Meena et al, 2010;Meena et al, 2013) and cancer (Park, et al, 2002;Hanley, et al, 2008;Premanathan, et al 2011). …”
Section: Introductionmentioning
confidence: 99%